MODEL PEMBELAJARAN BLENDED LEARNING PADA MASA NEW NORMAL DI TK GOLDEN KIDS - Hanifa Hafiza; Ninik Hidayati; Mira Shodiqoh (Alzam: Journal of Islamic Early Childhood Education, 2022)
The world experienced a shock, namely the Covid-19 virus which took many victims so that it almost paralyzed all activities in all sectors, from the economy, health, to education. Considering that an incident like this happened, the government decided to instruct the implementation of an online-based learning system that was simultaneously carried out by all educational institutions in Indonesia. The selection of this learning model is one of the joint decisions determined because it sees the situations and conditions that are in accordance with the learning model. The blended learning model includes three processes, namely planning, implementation, and evaluation. 1) At the planning stage of blended learning, such as determining learning applications using whatsapp, zoom, google meet and other applications, collecting data on student conditions and phone numbers by creating whatsapp groups, preparing lesson plans, preparing material, determining learning media. 2) At the stage of implementing blended learning, there are preliminary, core, and closing activities. Preliminary activities in the form of greetings, habituation, and attendance by calling the names of students. The main activity is the delivery of material and a question and answer session. The closing activity contains conclusions and asks whether students are happy. 3) At the evaluation stage of blended learning at Golden Kids Kindergarten, namely: limited face-to-face assessment and learning from home or distance learning